Community visioning programs processes and outcomes - Walzer, Norman.; Hamm, Gisele. (Community development research and practice series, 2012)
"Community visioning is key in helping local public officials and community leaders create a flourishing future for their cities, and is essential for the effective planning of these strategies. Visioning involves collaborative goal setting to motivate actions - of planners, citizens, and officials - in order to set up a strategic plan for the successful development of the community. The use of visioning since the 1980s has led to a wealth of information on the productivity of the paths it has taken. The contributors, all with experience working in the area, review the successes and failures of the strategies, and look at new innovations which are pushing the frontiers of community visioning. This review of the development of visioning focuses on small and medium sized communities in North America. It aims to guide citizens, local leaders and planners on what strategies are best to help them revitalise their communities and ensure a prosperous future"--